The application of Built-in Self Test (BIST) for embedded memory testing via MBISTArchitect - Nor Farahidah, Za’bah (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.